Effects of chitin nano-whiskers on the antibacterial and physicochemical properties of maize starch films. (20th August 2016) - Qin, Yang; Zhang, Shuangling; Yu, Jing; Yang, Jie; Xiong, Liu; Sun, Qingjie
Highlights: Effects of chitin nano-whiskers (CNWs) on maize starch–based films were investigated. Mechanical, opacity and barrier properties of the films were increased significantly. The To, Tp and ΔH of the nanocomposite films increased with CNW content increased. Films exhibit stronger antimicrobial activity against L. monocytogenes than E. coli . Abstract: We investigated the effects of chitin nano-whiskers (CNWs) on the antibacterial and physiochemical properties of maize starch–based films. The microstructures, crystalline structures, and thermal, mechanical and barrier properties of the nanocomposite films were characterized by using transmission electron microscopy, X-ray diffraction analysis, thermogravimetric, differential scanning calorimeter, and texture profile analysis. The tensile strength of the maize starch films increased from 1.64 MPa to 3.69 MPa (P < 0.05) after CNW reinforcement with up to 1%. The water vapor permeability of the nanocomposite films decreased from 5.32 × 10 −12 to 2.22 × 10 −12  g m −1  s −1  Pa −1 with the CNW content increasing from 0% to 2%. The onset temperature, peak temperature and the gelatinization enthalpy of the films containing CNWs were higher than those of the pure starch films. Furthermore, the nanocomposite films exhibited strong antimicrobial activity against Gram-positive Listeria monocytogenes but not against Gram-negative Escherichia coli .